The virtue of compassion in medical professions - Żołnierz, Joanna; Dobrowolska, Beata; Sak, Jarosław (Journal of Education, Health and Sport, 2018)
Introduction: The ethics of treatment virtues is currently one of the major ethical trends that enjoys great interest, especially among representatives of medical professions. Medical education is mainly based on character training i.e. preparing students for fulfilling determined roles and attitudes. It is based to exemplarism, mentoring and underlines the importance of master– student relations. A characteristic feature of these types of professions is the fidelity to ethos and moral values cultivated for hundreds of years. Objective: The aim of this article is to present the role of compassion virtue in the work of medical professionals and to provide examples of applying knowledge from this field to clinical and educational practice. Conclusions: The theory of virtues applied to the field of medical ethics allowing for the creation of a catalogue of moral dispositions necessary for adequate fulfilment of professional duties by health care providers. One of the most favoured virtues is that of compassion. This moral disposition is considered, by some theoreticians of the medical and nursing principles, a key and fundamental attribute of a good doctor and nurse. The virtue of compassion due to its typical components i.e. the moral and intellectual dimension, ensures the realization of the goal of medical profession, as well as expectations and needs of a specific patient, undergoing the treatment process. The fully developed virtue of compassion helps to maintain the balance between overprotection and excessive identification with the patient’s fate and lack of empathy and formalism. That way the virtue of compassion allows for pursuing medical goals by fulfilling all standards and guidelines in a caring and empathetic way.